Antibody responses in patients with rubella infection determined by passive hemagglutination, hemagglutination inhibition, complement fixation, and solid-phase radioimmunoassay tests. - Meurman, O H (1978)
Antibody responses in serial serum specimens collected from 31 patients with an acute rubella infection were determined by passive hemagglutination (PHA), hemagglutination inhibition (HI), complement fixation (CF), radioimmunoassay (RIA) immunoglobulin G (IgG), and RIA immunoglobulin M (IgM) tests to evaluate the effectiveness of these tests in diagnosing a recent infection. The HI, RIA IgG, and RIA IgM antibodies appeared almost simultaneously and reached the maximum level about 1 week after the onset of rash. Compared to these, the CF antibodies developed only slightly later, whereas the development of the PHA antibodies was much more delayed. The RIA IgM response was shown to be transient, lasting approximately 1.5 to 2.5 months postinfection. The results of this study indicate that demonstration of specific IgM antibodies is the best method for diagnosing a recent infection, one within 2 months after the onset of the illness. If an IgM test is not available, a combination of the HI and PHA tests is recommended.